Protective Effects of Biobran/MGN-3 Against Etoposide-Induced Immune Modulation and Hepatotoxicity in Male Rats - Ali M. Eldib, Heba E. Mostafa,, Rania E. Mufti, Zayed M Alnefaie, Osman Suliman, Amr Eldardear, Faris M. Elmahdi, Ibrahim H. Babikir, Sara M. Altom, Mohamed S. El-Gerbed, Mamdooh H. Ghoneum,, Sarah A. Almohammadi, Nafisah M. Alshamry, Asma O. Elkhalifa, Ibtihal N. Albalwai, Modhi A. Saleem, Heba S. Khalifa, Attalla F. El-kott,, Hytham M. Abdelatif, (Journal of Applied Pharmaceutical Science, 2025)
A variety of toxicities can result from treatment with chemotherapeutic drugs, including hepatotoxicity and impaired immunity. This study investigates the use of biobran as an adjuvant treatment against toxicity caused by the chemotherapy medication etoposide. 40 rats were divided into 4 groups to study the effects of etoposide (1 mg/kg body weight/day) and biobran (40 mg/kg body weight/day) over a duration of 6 weeks. Rats treated with etoposide exhibited elevated liver enzymes-aspartate aminotransferase and alanine aminotransferase indicating impaired liver function, decreased immunoglobulins M, G (IgM, IgG) revealing reduced immunoglobulin levels (IgM, IgG), indicating diminished antibody production, and elevated oxidative stress markers-malondialdehyde and nitric oxide compared to the control and biobran groups. Biobran supplementation in etoposide-treated rats partially mitigated these effects. In addition, etoposide decreased antioxidant markers-superoxide dismutase-catalase, and reduced glutathione, while biobran increased them significantly. Etoposide also increased the cytokines (IL-4, IL-6, IL-8, and IL-17) while decreased IL10, but biobran reversed these changes. Immunohistochemical analysis revealed elevated levels of pro-inflammatory cytokines-interleukin-1 beta-tumor necrosis factor-alpha and transforming growth factor-beta in etoposide-treated rats, which biobran restored to normal levels. Histopathological analysis also revealed liver damage in rats treated with etoposide, but not in those rats receiving biobran. Flow cytometry indicated that etoposide increased the activity of apoptotic markers caspase-3 and annexin, while Bcl-2 was decreased, effects that were reverted by biobran treatment. Results also showed that immune cell expressions of T cell surface molecules-CD4, CD8, and CD3 in etoposide-treated rats are mitigated by biobran. Collectively, the results of this research demonstrate that biobran can be an effective adjuvant agent to counter the toxic effects and immunological decline resulting from etoposide in cancer chemotherapy.
Keywords: Biobran, etoposide, immune modulation, hepatotoxicity, flow cytometry